2014
DOI: 10.1130/b31067.1
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between the thermal evolution of an orogenic wedge and its retro-wedge basin: An example from the Ukrainian Carpathians

Abstract: The Carpathian-Pannonian region is\ud made up of the wide extensional Pannonian\ud Basin surrounded by the Carpathian mountain\ud belt. The Pannonian Basin formed in the\ud Miocene by extension in a retro-wedge position\ud while thrusting was still active at the\ud Carpathian front. The Ukrainian region is\ud an ideal area to reconstruct the relationship\ud between the Pannonian Basin and the Carpathians,\ud due to the relatively simple structural\ud setting and to the progressive but neat\ud transition betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 61 publications
3
11
0
Order By: Relevance
“…This broad uplift is also supported by thermochronological and field studies in the Western Carpathians (e.g. Danišík et al 2010; Mazzoli et al 2010; Zattin et al 2011; Anczkiewicz, Środoń & Zattin, 2013; Andreucci et al 2013, 2015; Castelluccio et al 2015). The most probable candidates for such deep-seated processes are either oceanic slab roll-back and subsequent break-off, or delamination of the tectonically thickened European lithosphere (see Magni et al 2013).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 55%
See 1 more Smart Citation
“…This broad uplift is also supported by thermochronological and field studies in the Western Carpathians (e.g. Danišík et al 2010; Mazzoli et al 2010; Zattin et al 2011; Anczkiewicz, Środoń & Zattin, 2013; Andreucci et al 2013, 2015; Castelluccio et al 2015). The most probable candidates for such deep-seated processes are either oceanic slab roll-back and subsequent break-off, or delamination of the tectonically thickened European lithosphere (see Magni et al 2013).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 55%
“…These were integrated with existing gravity data (Geofyzika, unpub. report, 1999; Lenhardt et al 2007), recent and historic earthquake distributions (Reinecker & Lenhardt, 1999; Lenhardt et al 2007), lithospheric rheology (Andeweg & Cloetingh, 1998; Lankreijer et al 1999) and thermochronological studies (Mazzoli et al 2010; Andreucci et al 2013, 2015; Castelluccio et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Danišík et al [] pointed out that the early Miocene cooling ages detected by the AHe in some totally reset samples collected south of Tatra Mountains could be associated to the cooling after the Oligo‐Miocene sedimentary burial or magmatism or increased heat flow. A more recent study focused on the Ukrainian Carpathians and their relationship with the Pannonian Basin [ Andreucci et al ., ] suggested that magmatism had no significant impact on the thermal field of the inner part of the Ukrainian accretionary wedge and therefore on the thermal history of the analyzed rocks. Similar to the Ukrainian Carpathians, also, the thermal field of the Slovak IC is unlikely to have been perturbated by such magmatic activity.…”
Section: Low‐temperature Thermochronometric Datamentioning
confidence: 99%
“…The Carpathians are an arcuate mountain range located in the eastern continuation of the Alpine orogenic belt (Figure 1). Previous studies have shown that the overall Carpathian structure formed in response to the Triassic to Tertiary opening and closure of two oceanic realms by subduction and continental collision (details in Csontos & Vörös, 2004;Mațenco, 2017;Săndulescu, 1988;Schmid et al, 2019 Andreucci et al (2015); Mațenco (2017)). Note the different references used for Prut/ Dniestr, Siret and Focani base-levels.…”
Section: The Orogenic and Geomorphological Evolution Of The Eastern And Southeastern Carpathiansmentioning
confidence: 99%
“…First, the extent of the tecto-lithologic units is estimated using the compilation of 1:50,000, 1:200,000 and 1:500,000 geological maps (published by the Geological Institute of Romania) and the studies of Mațenco et al (2010) and Mațenco (2017). The Ukrainian section of the map has been completed and extrapolated using the extent of tectonic units in Andreucci et al (2015), with some spatial approximations and unit grouping to match nomenclature in the different datasets. We also acknowledge that local lithostratigraphic variation can occur within each tectonic unit, however we prioritize N-S continuity in our unit definition in order to track changes along the mountain range over adding localized sub-units.…”
Section: Rock Strengthmentioning
confidence: 99%